How Does AI Impact Vulnerable Patient Populations? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, offering unprecedented opportunities for improving diagnostics, treatment, and...
Keywords: AI Ethics in Healthcare; Impact; Vulnerable; Patient; Artificial Intelligence; Healthcare; Diagnostics